(untitled) (Biological Sciences - PJSIR, 2005)
Investigations have been carried out on the development of stabilized vegetable amylases for enzymatic desizing of woven fabric. Vegetable amylases from barley and germinated mango seeds were extracted and stabilized for industrial use. The desizing of woven cotton fabric was carried out with these amylases. Their desizing performance was also compared with commercially available enzymes. As a result of this study, highly active and stabilized amylases were obtained from barley and germinated mango seeds. The method used for the enzyme recovery was also noted to give good yield from both the sources of plant origin.